Strategi Pemasaran Usaha Kedai Kopi Cousin Coffee di Kelurahan Walian Kecamatan Tomohon Selatan Kota Tomohon - Ering, Christian Efata; Sondakh, Mex Frans Lodwyk; Laoh, Esry Olly Harryani (AGRI-SOSIOEKONOMI, 2024)
This study aims to determine the internal and external factors and marketing strategies of the Cousin Coffee shop business in Walian Village, Tomohon Selatan District, Tomohon City. Determination of informants in this coffee shop is using purposive sampling technique. Informants in this study were coffee shop owners, employees and customers. The data collected are primary data and secondary data using SWOT analysis. The results of this study indicate that Cousin Coffee coffee shop has internal strategic factors, namely strengths including strategic location, spacious place, there are many varied menu choices, and raw materials such as quality coffee. Weaknesses, namely social media related to promotional activities that have not been maximized, (private rooms) that are not yet available, lack of facilities such as wifi and other supporting facilities, and parking lots that are less spacious. And external strategic factors, namely opportunities including many residents around, building relationships with customers, attracting consumers with special offers, many relationships with people, and safe environmental conditions. Threats are the number of competitors, prices from competitors, unsatisfied consumer demand, the emergence of new coffee shops and offering promos and a better atmosphere, and unstable prices for basic commodities. The matrix of internal and external strategic factors shows a total value of 3.10 and 2.76, respectively. With the total value of the internal and external strategic factor matrix, it shows that this coffee shop is in quadrant 1, namely an aggressive strategy.